DESIGN OF L-BAND PYRAMIDAL HORN ANTENNA FOR ELECTRONIC SUPPORT MEASURE (ESM) - Widi Anggun Fitriana; Budi Syihabuddin; Yuyu Wahyu; Heroe Wijanto (PROSIDING SNAST, 2018)
Radar is a part of an electronic element that consists of electromagnetic waves to detect and determine the location of an object. The Electronic Support Measure (ESM) is part of electronic warfare to search for intercepting, identifying and locating radiated electromagnetic energy for the purpose of immediate threat recognition. It should be able to sense the working frequency of 1-12 GHz, including at L-Band which has 1 - 2 GHz bandwidth. The horn antenna has a relatively large gain so that the electromagnetic wave reception is more sensitive and accurate. It can be used as receiver antennas in ESM design. However, it is important to adjust the dimensions of the waveguide, the horn antenna and the monopole to obtain the appropriate antenna specification. This study tells about designing an L-Band horn pyramid antenna that can be applied to ESM. Antenna consists of rectangular waveguide, horn pyramid and monopole. The waveguide material and the pyramid horn made from 0.7 mm brass plates. While the monopole material is a 12 mm copper rod with length, placed 7 cm from the backside of the waveguide. Optimization results obtained 1.19 GHz bandwidth at L-Band, 13.74 dB gain, 1.26 VSWR , 18.87 dB Return Loss and unidirectional radiation pattern. These specifications comply the ESM antenna specifications.